2019
DOI: 10.1016/j.psychres.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain in Major Depressive Disorder: Linking appetite and disordered eating to leptin and ghrelin.

Abstract: Major Depressive Disorder (MDD) involves changes in appetite and weight, with a subset of individuals at an increased risk of weight gain. Pathways to weight gain may include appetite disturbances, excess eating, and dysregulation of appetite hormones. However, little research has simultaneously examined relationships between hormones, eating behaviours and MDD symptoms. Plasma ghrelin and leptin, biometrics, eating behaviours and psychopathology were compared between depressed (n = 60) and control (n = 60) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…These findings are consistent with the notion that rapid post-surgery weight loss only temporarily aids the remission of depression, which later re-occurs once the surgical benefits decline ( 43 , 50 , 51 ). Similarly, studies have shown that depressed mood is associated with unhealthy lifestyle habits ( 52 ), emotional eating, and loss of control (LOC) eating [e.g., ( 53 , 54 )]. In particular, post-surgery depressive symptoms have been associated with ED and weight recidivism ( 42 , 55 57 ).…”
Section: Depressionmentioning
confidence: 99%
“…These findings are consistent with the notion that rapid post-surgery weight loss only temporarily aids the remission of depression, which later re-occurs once the surgical benefits decline ( 43 , 50 , 51 ). Similarly, studies have shown that depressed mood is associated with unhealthy lifestyle habits ( 52 ), emotional eating, and loss of control (LOC) eating [e.g., ( 53 , 54 )]. In particular, post-surgery depressive symptoms have been associated with ED and weight recidivism ( 42 , 55 57 ).…”
Section: Depressionmentioning
confidence: 99%
“…Furthermore, there is an extensive literature identifying that depression is associated during the isolation with an increased risk of overeating (Baenas et al, 2020;Mengin et al, 2020). Recent studies have confirmed the relationship between depressed mood and "pathological" eating habits, depression would be associated with an increased risk of overeating (Trojanowski and Fischer, 2018;Mills et al, 2019Mills et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies indicate that some psychological traits are associated with disordered eating [10] and weight gain [11], the mechanisms underlying the relationships between these factors have not yet been exhaustively investigated. Hunger and satiety hormones such as ghrelin and leptin, and their involvement in the suppression activity of stress responses by Hypothalamic-Pituitary-Adrenal (HPA) axis are hypothesized to play a role in the relationship between appetite/weight changes and psychological disorder onset [12]. Elevated levels of leptin have been associated with obesity, psychological distress, increasing systemic inflammation, increasing risk in the development of several maligniances (colon, ovarian cancer, prostate, and breast cancers) [13].…”
Section: Introductionmentioning
confidence: 99%